Analisis Drop Tegangan pada Instalasi Gedung Sipil Menggunakan Data DBMS (Database Management System) - Sukamdi; Sigit Setya Wiwaha; Agista Ilham Aditama; Sendy Mochtar; Yessy Ema Wista Nainggolan (Elposys: Jurnal Sistem Kelistrikan, 2021)
The results of the voltage drop calculation from the MDP panel to the SDP under maximum load conditions (100% loading) show that the largest voltage drop occurs on the Hyundai Lift Power Panel by 0.51%, due to the distance of the conductor to the PP Lift Hyundai being the farthest and the cross-sectional area and the magnitude of the load current being larger than other panels. From the analysis of the comparison of manual voltage drop calculation results against Ecodial simulation, there is an error of 9.8%, while against ETAP simulation there is an error of 5.88%. Based on the results of voltage drop calculations and analysis with manual calculations and Ecodial and Etap simulations in civil buildings, the percentage of voltage drop results is in accordance with PUIL 2011 Chapter 2.2.3 and IEC 60364-5-52 Table G.52.1 standards so there is no need to make voltage drop repairs because electrical conditions on each floor of civil buildings are still in normal condition.